A miniaturized interdigital microstrip bandpass filter - Huang, K; Hyland, D; Jenkins, A; Edwards, D (1999)
A 2.4 GHz three-stage mlcrostrip bandpass filter was designed using a miniaturized interdigital capacitor structure to reduce the configuration in size. The filter was simulated by a finite element method software and then fabricated using TBCCO superconducting films on 20 mm x 20 mm x 0.5 mmt MgO substrates. It was generated by photolithographic and wet etching process and packaged in a brass box. The bandwidth is 4% and the passband insertion loss of the filter was measured to be -0.4 dB at 77 K. The return loss is better than -8 dB. In particular, this filter has a sharper performance at its edge of fundamental pass band. © 1999 IEEE.